Penatalaksanaan Fisioterapi Pada Kasus Acute Myocardial Infarction : Case Report - Ajeng Sabtorini; Umi Budi Rahayu; Kadek Agustini Aryani (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Acute Myocardial Infarction (AMI) is a critical medical condition that requires comprehensive rehabilitation to restore cardiac function and quality of life. This study presents a case report of a 54-year-old female patient post-PCI following subendocardial myocardial infarction. The physiotherapy intervention was conducted during phase 2 of cardiac rehabilitation in four sessions, consisting of warm-up (cardiac exercise), main training (walking and treadmill), and cool-down (ergocycle). Evaluation included the 6-Minute Walk Test (6MWT), Borg Scale, vital signs, and thoracic cage measurements. Results showed an increase in walking distance from 462 meters to 500 meters, improved METs, decreased Borg Scale score, and greater thoracic expansion. These findings suggest that phase 2 physiotherapy intervention effectively enhances functional capacity and physical activity tolerance in post-AMI patients.